Social Sensibility. Simmel, the Senses, and the Aesthetics of Recognition - Carnevali, Barbara (Simmel Studies)

(untitled) (Georg Simmel Gesellschaft, 2017)
In this article, I sketch a theory of social sensibility building on Simmel’s Sociology. I focus on the sense of smell and its “distancing” function, and I develop Simmel’s insights in line with the phenomenological theory of the “oral sense” (Oralsinn). Notions like atmosphere and Stimmung allow me to shed light on the almost subliminal functioning of social evaluation: sensible inclinations pre-condition deeply social relations. In addition, I focus on the link between recognition and esteem (Anerkennung and Schätzung) in its active meaning (how we value others through our feelings) as well as in its passive meaning (how we strive to please and how the quest for recognition is part of the search for distinction). I conclude by suggesting the need for a reciprocal integration between Simmel’s and Bourdieu’s reflections.